Penentuan kadar flavonoid total ekstrak etanol kayu kuning (Arcangelisia flava (L.) Merr. ) dan uji antibakteri Staphylococcus aureus . - Nuraida, Nuraida; Ridwanto, Ridwanto; Daulay , Anny Sartika; Nasution , Haris Munandar (Journal of Pharmaceutical and Sciences, 2024)
Indonesia has a diversity of plant species used as traditional medicine, one of which is yellow wood (Arcangelisia flava (L.) Merr.), this yellow wood is antibacterial, anti-inflammatory, antiseptic and antipyretic. It is known that yellow wood contains saponins, flavonoids, alkaloids, tannins, and steroids that can treat malaria, fever, rheumatism and itching. This study aims to determine the value of total flavonoid content contained in yellow wood extract in various ethanol concentrations (50%, 70% and 96%) and to determine the antibacterial inhibition zone in yellow wood extract. The stages of this study include processing plant materials, making ethanol extracts of yellow wood with ethanol concentrations of 50%, 70% and 96% using the maceration method then the extract obtained is concentrated with a rotary evaporator, examining characteristics, phytochemical screening, determining the total flavonoid content of yellow wood extract concentrations (50%, 70% and 96%) by UV-Vis spectrophotometric method and antibacterial test of Staphylococcus aureus  by diffusion method. The results showed that ethanol extract of yellow wood contains alkaloid, flavonoid, tannin, saponin, and steroid/terpenoid compounds. The results of the determination of total flavonoid content in yellow wood extract at 50% concentration amounted to 0.815200888 ± 0.02445546 mg QE/g, 70% concentration amounted to 1.0660462967 ± 0.03265799 mg QE/g and at 96% concentration amounted to 1.6781149 ± 0.0085 mg QE/g. Antibacterial test on 96% yellow wood extract obtained an inhibition zone of 18.05 mm with a strong category.